Role of volcanism and impact heating in mass extinction climate shifts - Kunio Kaiho (Scientific Reports, 2024)
Abstract This study investigates the mechanisms underlying the varied climate changes witnessed during mass extinctions in the Phanerozoic Eon. Climate shifts during mass extinctions have manifested as either predominant global cooling or predominant warming, yet the causes behind these occurrences remain unclear. We emphasize the significance of sedimentary rock temperature in comprehending these climate shifts. Our research reveals that low-temperature heating of sulfide leads to global cooling through the release of sulfur dioxide (SO2), while intermediate-temperature heating of hydrocarbons and carbonates releases substantial carbon dioxide (CO2), contributing to global warming. High-temperature heating additionally generates SO2 from sulfate, further contributing to global cooling. Different degrees of contact heating of the host rock can lead to different dominant volatile gas emissions, crucially driving either warming or cooling. Moreover, medium to high-temperature shock-heating resulting from asteroid impacts produces soot from hydrocarbons, also contributing to global cooling. Large-scale volcanic activity and asteroid impacts are both events that heat rocks, emitting the same gases and particles, causing climate changes. The findings elucidate the critical role of heating temperature and heating time in understanding major climate changes during mass extinctions.